Duration of Access of Canadian Immigrants to the First Job in Intended Occupation - Grenier, Gilles; Xue, Li (Université d'Ottawa | University of Ottawa, 2009)
Using detailed information on employment trajectory provided by the Longitudinal Survey of Immigrants to Canada (LSIC), this study examines labour market outcomes of recent immigrants in terms of duration of access to the first job in their intended occupation, as determined by a question in the first wave interview on labour market intentions. The matching between actual and intended occupations is obtained from the first two digits of National Occupational Classification codes, which consider successively occupation type and skill level. Using a Cox proportional hazards model, the study investigates the roles of factors related to human and social capital in speeding up the matching process of actual and intended occupations. It is found that the initial year in Canada is critical for an immigrant to land a job in intended field; after that period, the hazards of finding employment in intended occupation flatten down. In general, those with intention to work in non-professional jobs, such as sales and services, trades, transport and equipment operators, primary industry, and processing and manufacturing occupations, enter the first job in intended occupation more quickly. The results also show that education, English language ability, Canadian work experience and friend networks facilitate access to intended occupation.. / À partir de renseignements détaillés fournis par l’Enquête longitudinale auprès des immigrants du Canada (ELIC) sur les parcours professionnels, cette étude s’intéresse au temps qu’il faut aux nouveaux immigrants pour occuper un premier emploi dans la profession qu’ils envisagent d’exercer, celle-ci étant déterminée par une question posée dans le cadre de la première série d’entrevues. Le jumelage entre la profession réelle et celle envisagée est réalisé au moyen des deux premiers chiffres du code de la Classification nationale des professions, qui indiquent tour à tour le genre et le niveau de compétence. Avec un modèle de hasards proportionnels de Cox, l’étude permet de déterminer la mesure dans laquelle le capital social et le capital humain contribuent à accélérer le processus par lequel la profession envisagée devient la profession réelle. Il ressort que la première année au Canada est cruciale pour l’obtention d’un emploi dans le domaine envisagé; après cette période, les chances de trouver un emploi dans le domaine souhaité diminuent. En général, les personnes qui envisagent d’exercer une profession autre que libérale, par exemple dans le domaine des ventes et services, des métiers, de la conduite de matériel de transport, dans le secteur primaire ainsi que dans le domaine de la transformation et de la fabrication, obtiennent plus rapidement un emploi dans la profession envisagée. Les résultats de l’étude montrent par ailleurs que la scolarité, la connaissance de l’anglais, le fait de posséder une expérience de travail au Canada et d’y compter un réseau d’amis sont autant de facteurs qui aident à trouver un emploi dans le domaine souhaité.
Keywords: Immigrants; Occupation; Labour market; Canada; Immigrants; profession; marché du travail; Canada